2015
DOI: 10.1590/abd1806-4841.20153969
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study for efficacy and safety evaluation of a fixeddose combination gel with adapalen 0.1% and benzoyl peroxide 2.5% (Epiduo® for the treatment of acne vulgaris in Brazilian population

Abstract: BACKGROUNDThe current options for the treatment of acne vulgaris present many mechanisms of action. For several times, dermatologists try topical agents combinations, looking for better results.OBJECTIVESTo evaluate the efficacy, tolerability and safety of a topical, fixed-dose combination of adapalene 0.1% and benzoyl peroxide 2.5% gel for the treatment of acne vulgaris in the Brazilian population.METHODSThis is a multicenter, open-label and interventionist study. Patients applied 1.0 g of the fixed-dose comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
8
0
2
Order By: Relevance
“…showed that the AD and BPO treatments were helpful in ameliorating AV and less expensive than other treatments. [3132] Our study shows the same effects in two groups which is in accordance with the discussed articles.…”
Section: Discussionsupporting
confidence: 91%
“…showed that the AD and BPO treatments were helpful in ameliorating AV and less expensive than other treatments. [3132] Our study shows the same effects in two groups which is in accordance with the discussed articles.…”
Section: Discussionsupporting
confidence: 91%
“…These side effects appear in the beginning 14,27 of treatment and may be a drawback in general treatment with BPO in conjunction with shoulder surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The results of MNLG were significantly comparable to 1% clindamycin‐treated side which also significantly reduced the comedone and inflammatory acne lesions up to 55.33% and 64.16%, respectively. Distinctively, the efficacy of MNLG application with 2.5% BPO in this study was comparable to the standard combination treatment of 0.1% adapalene and 2.5% BPO, with the decreasing of both comedone lesions (73%) and inflammatory acne lesions (73.9%) over the 12 weeks of treatment . However, the efficacy could be the synergistic effect of BPO and MNLG, because the BPO monotherapy also showed the efficacy in the treatment of acne with the median reduction of 55.6% and 44.1% in inflammatory lesion and noninflammatory lesions count after 12‐week treatment, respectively…”
Section: Discussionmentioning
confidence: 47%